2021
DOI: 10.3390/w13223269
|View full text |Cite
|
Sign up to set email alerts
|

Application of Geostatistical Tools to the Geochemical Characterization of the Peloritani Mts (Sicily, Italy) Aquifers

Abstract: Sources of groundwater contaminants in inhabited areas, located in complex geo-tectonic contexts, are often deeply interlocked, thus, making the discrimination between anthropic and natural origins difficult. In this study, we investigate the Peloritani Mountain aquifers (Sicily, Italy), using the combination of probability plots with concentration contour maps to retrieve an overall view of the groundwater geo-chemistry with a special focus on the flux of heavy metals. In particular, we present a methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…For instance, De Vivo et al (1993) stressed the presence of anomalous contents of As, Hg, Sb, Zn and Pb in stream sediments from this area, whereas Dongarrà et al (2009) found high As concentrations in waters from mineralised areas. A geogenic source for the As contamination detected in the Peloritani Mountains was also suggested by Cangemi et al (2021), agreeing with previous results of Cosenza et al (2015) who reported high PTE content in soils from Fiumedinisi, Budali and Alì, related to the weathering of ore deposits and mine wastes.…”
Section: Introductionsupporting
confidence: 90%
“…For instance, De Vivo et al (1993) stressed the presence of anomalous contents of As, Hg, Sb, Zn and Pb in stream sediments from this area, whereas Dongarrà et al (2009) found high As concentrations in waters from mineralised areas. A geogenic source for the As contamination detected in the Peloritani Mountains was also suggested by Cangemi et al (2021), agreeing with previous results of Cosenza et al (2015) who reported high PTE content in soils from Fiumedinisi, Budali and Alì, related to the weathering of ore deposits and mine wastes.…”
Section: Introductionsupporting
confidence: 90%